Penatalaksanaan Holistik Asma Eksaserbasi Pada Pasien Perempuan Usia 39 Tahun dengan Pendekatan Kedokteran Keluarga - fitria saftarina; Hanifa Yuniasari (CV. Jasa Sukses Abadi, 2021)
Asthma is a chronic respiratory disease with a complex multifactorial disorder and its etiology is associated with the interaction between genetic susceptibility, host factors, and environmental exposures. Asthma can be considered a significant public health problem. Recurrent asthma symptoms often cause difficulty, daytime fatigue, reduced activity and productivity, and increase absenteeism from school and work. Asthma management must be with continuous monitoring to achieve controlled asthma, so it is necessary to manage patients holistically and comprehensively to improve patients’ quality of life. This study is a case report of asthma exacerbation in a woman who has various internal and external risk factors that influence the patient's disease. Primary data were obtained through history taking, physical examination and support during home visits. Secondary data obtained from the patient's medical record. Management of patients with asthma exacerbations is carried out comprehensively with the concept of a patient-centered, family-focused, and community-oriented approach. Medical management is in the form of relieving drugs and asthma control drugs. Non-medical management is in the form of education about asthma, including explaining and asking patients to identify and avoid asthma triggers. The results of the evaluation showed changes in attitudes in reducing the risk of exacerbations and improvements in asthma control as assessed by the Asthma Control Test.